Case of Secondary Tics Associated With Olanzapine in an Adult - Mills, Eric W.; Shaffer, Lindsay S.; Goes, Fernando S.; Sawa, Akira; Nucifora, Frederick C. (Frontiers in Psychiatry, 2017)
Atypical antipsychotic medications, such as risperidone, aripiprazole, and olanzapine, have utility in treating motor tics, particularly in Tourette syndrome. In rare cases, atypical antipsychotic medications have been associated with adult-onset motor tics. Such adverse drug reactions have been documented in response to quetiapine, aripiprazole, and amisulpride. Here, we report, to our knowledge, the first case of adult-onset motor tics related to olanzapine administration.